Durability of Fiber-Reinforced Polymer (FRP) Bars: Progress, Innovations and Challenges Based on Bibliometric Analysis - Nassif, Nadia; Junaid, M. Talha; Maalej, Mohamed; Altoubat, Salah; Barakat, Samer A. (Civil Engineering Journal, 2024)
This review systematically examines the literature on the Fiber-Reinforced Polymer (FRP) bars durability in concrete matrices using bibliometric analysis to understand progress, innovations, and challenges. The objective is to explore the durability of FRP bars, which are recognized for their strength-to-weight ratio, corrosion resistance, and non-conductivity, as a potential substitute to conventional steel reinforcement. Methods involved employing bibliometric tools such as Biblioshiny and VOSviewer to analyze trends, collaboration patterns, and the global distribution of publications. Findings reveal an increase in research activity over the past two decades, significant international collaboration, and leading contributions from key countries. Critical environmental factors like alkalinity, thermal conditions, and chemical aggressors affecting the interface of fiber-matrix mechanical properties were highlighted. Advances in predictive modeling for long-term behavior conditioned FRP bars are studied, steering future research towards improved durability and sustainable construction practices. This study contributes novelty by providing a comprehensive bibliometric perspective on FRP bar durability, identifying emerging trends, and suggesting areas for future suggested research to enhance the reliability and application of FRP bars in construction. Doi: 10.28991/CEJ-SP2024-010-09 Full Text: PDF